Enzymatic Synthesis of Palm Based Amino Acid Esters - Soo, Ee Lin (2003)
Acyllysines were successfully prepared from reactions of free fatty acids (FFAs) (palmitic acid, PA; oleic acid, OA), triglycerides (TGs) (tripalmitin, TP ; triolein, TO) and palm oil fractions (palm olein, PO; palm kernel olein, PK O) with the unprotected amino acid, L-lysine, using enzymes as biocatalyst in an organic solvent system. Such a selective enzymatic route obviates the fastidious regime of substrate activation/protection required in chemical synthesis. Preliminary detection and identification of reaction products were facilitated by thin layer chromatography (TLC) while subsequent quantitative studies on main and interactive effects of parameters governing the reactions were conducted with TLC-photodensitometry. Enzyme screening revealed Lipozyme IM to be the most efficient biocatalyst for the reactions. By varying one-parameter-at-a-time, 70°C was shown to be the optimal temperature, hexane, the most suitable solvent, and, 5:1 (PA:L-lysine), 3:1 (OA:L-lysine), 1:1 (TP:L-lysine), 1:3 (TO:L-lysine), 1:1 (pO:L-lysine) and 1:I(PKO:L-lysine) the respective optimal substrate molar ratios. To reach equilibrium, reactions of FF As and TGs with L-lysine required 4 days while those of the more complex PO and PKO required 6 days. Higher biocatalyst amounts improved all reactions (except that of TP with L-lysine), as did higher amounts of molecular sieves added to reactions ofOA and TO with L-lysine.